Development of Gray Scale Image Processing computing Technique to Remove the Unwanted Frequency Patches on Sodar Facsimiles - Hareesh Babu, M; Bala Naga Bhushanamu, M; Raju, DSSN; Purnachandra Rao, M (International Journal of Computer Sciences and Engineering, 2025)
Gray Scale Image Processing (GSI) technique has developed using MATLAB’s Digital Signal Processing toolbox to remove the unwanted frequencies present in the SODAR facsimiles and also to enhance the pixel quality (intensity) of the facsimiles for a better view. In general, the sources of these noises (unwanted frequencies) are airplanes, Choppers, Hi-frequency sound systems and man-made noises nearby SODAR antenna. Already some filtering techniques like Gaussian filter, median filter, and other DSP filter techniques are employed to remove the noises from facsimiles but these techniques are incapable of enhancing the pixel clarity. This GSI computing techniques could be applied directly to SODAR facsimiles, which is not possible with other filtering techniques. The beauty of the technique is that time was taken to complete the process within 10 to 20 seconds. Here in this paper, all mathematical computing techniques are designed and developed through MATLAB.